Endovascular occlusion of primary major pelvic arteriovenous fistula using patent ductus arteriosus occluder. (March 2016) - Xu, L; Wu, Z; Qu, L; Burchell, S
The aim of the present study was to investigate the effects and safety of a patent ductus arteriosus occluder (PDAO) in the management of major abdominal arteriovenous fistula. A 56-year-old man was admitted into our hospital, presenting with impeded defecation and claudication. Computed tomographic angiography (CTA) was conducted upon admission, which revealed an aneurysm-like lesion, with the left internal iliac artery as its feeding artery. Super-selective embolization treatment was accomplished using a single PDAO. The results of the CTA at follow-up showed no recanalization of the lesion and that a PDAO was at the site. The patient had no pelvic ischemia complications.